IMPLEMENTATION OF PRE MARITAL AGREEMENTS FOR THE COMMUNITY (Case Study at the Office of Notary Lenny Wibowo, S.H., M.Kn., Batu City) - Navisatul Zahro; Muhammad Muhibbin; Sunardi Sunardi (SOSIOEDUKASI, 2026)
The aim of this study is to analyze the causes, implementation, and impact of marriage agreements on both spouses in accordance with the provisions of the Indonesian Civil Code and the Code of Law. This research is an empirical study using an empirical Juridical approach method. The data analysis used is Qualitative data analysis. The type of data used is secondary legal data consisting of primary, secondary, and tertiary legal materials. This research is descriptive in nature, and the selection of this method is because the researcher wants to study legal issues, facts, and phenomena that are developing in society by analyzing the existing situations. In this research, the technique used is qualitative technique. The findings lead to the conclusion that a marriage agreement is still rarely encountered because society still thinks that marriage agreements are taboo and have difficulty or confusion in making such agreements. For most people, marriage agreements are still seen as being only about property issues. In fact, marriage agreements are not only used for property or property separation, but marriage agreements can create an agreement that discusses everything as long as it does not violate the law and religious laws. Furthermore, marriage agreements can greatly assist in the sustainability of a harmonious family. They also provide legal protection in case of disputes in marital life.